Epstein-Barr Virus-Associated Lymphoproliferative Disorders: Review and Update on 2016 WHO Classification - Hyun-Jung Kim; Young Hyeh Ko; Ji Eun Kim; Seung-Sook Lee; Hyekyung Lee; Gyeongsin Park; Jin Ho Paik; Hee Jeong Cha; Yoo-Duk Choi; Jae Ho Han; Jooryung Huh (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Epstein-Barr virus (human herpesvirus-4) is very common virus that can be detected in more than 95% of the human population. Most people are asymptomatic and live their entire lives in a chronically infected state (IgG positive). However, in some populations, the Epstein-Barr virus (EBV) has been involved in the occurrence of a wide range of B-cell lymphoproliferative disorders (LPDs), including Burkitt lymphoma, classic Hodgkin's lymphoma, and immune-deficiency associated LPDs (post-transplant and human immunodeficiency virus-associated LPDs). T-cell LPDs have been reported to be associated with EBV with a subset of peripheral T-cell lymphomas, angioimmunoblastic T-cell lymphomas, extranodal nasal natural killer/T-cell lymphomas, and other rare histotypes. This article reviews the current evidence covering EBV-associated LPDs based on the 2016 classification of the World Health Organization. These LPD entities often pose diagnostic challenges, both clinically and pathologically, so it is important to understand their unique pathophysiology for correct diagnoses and optimal management.